Fast identification of Wiener‐Hammerstein systems using discrete optimisation. Issue 25 (1st December 2014) - Schoukens, M.; Vandersteen, G.; Rolain, Y.; Ferranti, F.
Abstract : A fast identification algorithm for Wiener‐Hammerstein systems is proposed. The computational cost of separating the front and the back linear time‐invariant (LTI) block dynamics is significantly improved by using discrete optimisation. The discrete optimisation is implemented as a genetic algorithm. Numerical results confirm the efficiency and accuracy of the proposed approach.